The association between educational resource utilization and knowledge/self-management among patients with Type 2 Diabetes in Pune, India. Issue 4 (October 2016) - Javalkar, Karina; Williamson, Nicole; Vaidya, Saleena; Vaidya, Abhijit; Ferris, Maria
Abstract: Aims: Patients utilize a variety of sources to learn about their condition. This study assessed the association of these resources with patient knowledge, adherence, and physiologic outcomes. Methods: Adults with Type 2 diabetes recruited at an outpatient clinic in Pune, India provided IRB-approved consent and completed surveys measuring diabetes knowledge, self-management, and educational resource utilization. Lab values were obtained from the patient's medical record. Statistical analysis was conducted in SPSS to determine the association between educational resources and outcomes. Results: We enrolled 82 patients with a mean age of 58.3 years. The most commonly used resource was books/pamphlets. The use of television and books/pamphlets as sources of information was significantly associated with greater knowledge and self-management. Use of books and pamphlets and peers with diabetes was associated with lower fasting and postprandial blood glucose. Regression analyses controlling for age, gender, and years with diabetes revealed that use of newspapers and magazines, books and pamphlets, and television were predictors of overall diabetes knowledge and nutrition knowledge. The use of television as a source of information was a predictor of the hours exercised per week. Conclusions: Resources such as books and pamphlets, newspapers and magazines, and television are common ways that people with diabetes learn about their medical conditions. The use of television as a source of information predicted the greatest number of positive outcomes among patients, followed by use of books and pamphlets. These methods should be further explored in order to understand how their benefit may be maximized for patients.